A posteriori diagnosis of DRESS syndrome induced by diazoxide in a patient with an insulinoma: a case report and review of the literature - Lassoued, Najoua; Alaya, Wafa; Arfa, Sondos; Korbi, Mouna; Lassoued, Ines; Amor, Soumaya Ben; Zaouali, Fatma; Farhat, Zayneb; Chelly, Jihen; Habib Sfar, Mohamed (Frontiers in Medicine, 2023)
The Drug Rash with Eosinophilia and Systemic Symptoms (DRESS) syndrome can be potentially life-threatening .The diagnosis is sometimes difficult since the clinical manifestations may be incomplete or nonspecific .Insulinoma is a rare neuroendocrine tumour of the pancreas. Medical therapy may be needed when surgery is contraindicated, delayed or refused. Diazoxide is widely used to control hypoglycemia in patients with insulinoma.We report a clinical case of an insulinoma in a 85-year-old patient treated with diazoxide with a fatal outcome due to a delayed diagnosis of a DRESS syndrome. This is the first case of DRESS syndrome reported after using diazoxide for insulinoma treatment in our knowledge.